Selective inhibition of factor inhibiting hypoxia-inducible factor. - McDonough, M; McNeill, L; Tilliet, M; Papamicaël, C; Chen, Q; Banerji, B; Hewitson, K; Schofield, C (2005)
A set of four non-heme iron(II) and 2-oxoglutarate-dependent enzymes catalyze the post-translational modification of a transcription factor, hypoxia inducible factor (HIF), that mediates the hypoxic response in animals. Hydroxylation of HIF both causes its degradation and limits its activity. We describe how the use of structural data coupled to solid-phase synthesis led to the discovery of a selective inhibitor of one of the HIF hydroxylases. The inhibitor N-oxalyl-d-phenylalanine was shown to inhibit the HIF asparaginyl hydroxylase (FIH) but not a HIF prolyl hydroxylase. A crystal structure of the inhibitor complexed to FIH reveals that it binds in the 2OG and, likely, in the dioxygen binding site. The results will help to enable the modulation of the hypoxic response for the up-regulation of specific genes of biomedical importance, such as erythropoietin and vascular endothelial growth factor.